2018
DOI: 10.1080/02786826.2018.1424316
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroxyacetone levels in electronic cigarettes: Wick temperature and toxin formation

Abstract: Recently, we reported the presence of dihydroxyacetone (DHA), the active ingredient in sunless tanners, in the aerosol of an electronic cigarette. DHA has been shown to react with DNA in vitro. The FDA restricts the use of DHA to external application only. It states that it should not be inhaled, ingested, or come into contact with any areas containing mucous membranes, due to unknown risk. Herein, the quantification of DHA in the aerosols of three brands of e-cigarettes has been carried out. These included tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…At a temperature of 318°C, formaldehyde, acetaldehyde, acetone and acrolein were generated [ 18 ]. In the current study, we expand on our previous report on e-cigarette wicking properties [ 7 ], wherein we had shown that the stability of the wick temperature during aerosolization served as a predictor of the degree of PG/GL degradation.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…At a temperature of 318°C, formaldehyde, acetaldehyde, acetone and acrolein were generated [ 18 ]. In the current study, we expand on our previous report on e-cigarette wicking properties [ 7 ], wherein we had shown that the stability of the wick temperature during aerosolization served as a predictor of the degree of PG/GL degradation.…”
Section: Introductionmentioning
confidence: 91%
“…Factors such as puff volume [ 4 ], e-liquid consumed [ 5 ] and power output [ 6 ] are known to correlate to toxin levels intra-device; however, methods for understanding inter-device levels are still needed. For instance, ten times lower toxin levels were reported in the aerosols produced by an e-cigarette operated at 50 W compared to a different e-cigarette operated at 10 W [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vreeke et al [35] observed that acrolein and acetaldehyde remained below the limit of detection when power increased from 55 W to 65 W on a sub-ohm (<1 ohm resistance) heating coil, but these toxicants increased when power increased from 9 W to 11 W on a supra-ohm (>1 ohm resistance) heating coil. Vreeke et al [34] found that device temperature increases with increasing power and corresponds directly to dihydroxyacetone (DHA) production. Pankow et al [50] observed that benzene concentrations in aerosol increased with increasing wattage from 6 W to 13 W on one device, but remained undetectable when wattage increased from 6 W to 20 W on a different device.…”
Section: Carbonyls/vocsmentioning
confidence: 99%
“…Pankow et al [50] reported that benzene concentrations were largely undetectable in an ENDS with a single vertical coil with a cotton wick, but were more readily detected with a single horizontal coil with a silica wick. Vreeke et al [34] observed that aerosol concentrations of DHA were directly proportional to the mass of aerosolized VG:PG, but a vertical coil produced less DHA than a horizontal coil.…”
Section: Plos Onementioning
confidence: 99%
“…Other chemical compounds are generally added to the e-liquid formulation, such as nicotine and (in smaller quantities) flavor, water, and ethanol primarly 2 4 . The chemical composition of the aerosol produced by the EC depends on several parameters such as the delivered power, the ingredients of the e-liquid, or the puffing conditions, number of puffs, volume and duration, and features of airflow, among others 5 7 . The aerodynamic diameter of the airborne droplets generated by ECs has a noticeable impact on the nicotine delivery to the vapers.…”
Section: Introductionmentioning
confidence: 99%